Thermal conductivity of graphene/poly(vinylidene fluoride) nanocomposite membrane. (15th January 2017) - Guo, Hong; Li, Xin; Li, Baoan; Wang, Jixiao; Wang, Shichang
Abstract: Compared to metallic materials for the use of heat exchanger, polymeric materials have been enjoyed superior advantages such as corrosion resistance, low density, fouling resistance, facile processing and low cost. Poly(vinylidene fluoride) (PVDF) is semi-crystalline thermoplastic polymer with excellent corrosion resistance, thermal and electrochemical stability. In order to improve its thermal conductivity, graphene/PVDF composites were prepared and studied in this paper. The graphene was doped in PVDF matrix for preparing graphene/PVDF composite membranes. In addition, electric field was applied for graphene alignment during membrane formation. The morphology, structure, thermal conductivity and tensile strength of the composite membranes before and after alignment were characterized and analyzed. The tensile strength and thermal conductivity of composite membranes were significant improved with the addition of graphene. This tendency was further enhanced by the application of electric field. When graphene content was 20 wt%, the thermal conductivity of the composite membrane was increased by 212% than that of pure PVDF and it was further enhanced to 226% after applying electric field. The maximum tensile strength was obtained when graphene content was 3 wt%. This study may be beneficial to further development of thermal conductive polymeric materials. Graphical abstract: Highlights: Electric field was applied for the orientation of composite membrane structure during membrane formation. After the alignment with electrical field, the arrangement of graphene was perpendicular to the membrane surface. The thermal conductivity of the composite membrane was increased by 212 %, with graphene content of 20 wt%. The thermal conductivity of the composite membranes was further enhanced by the application of electric field.